An insight into the chemical composition of ground ivy (Glechoma hederacea L.) by means of macrocomponent analysis and fractionation of phenolic compounds - Šeremet, Danijela (Array, 2020)
Ground ivy (Glechoma hederacea L.) has been used for generations in folk medicine to treat various diseases. Up until today, the information about its chemical and bioactive composition is still rather incomplete. The aim of this study was to evaluate macro- and microcomposition of ground ivy including the polyphenolic profile. In the present study, different phenolic fractions (free soluble, esterified, glycosylated and insoluble-bound phenolic fractions) of ground ivy were prepared and analysed using spectrophotometric methods (total phenolic content and antioxidant capacity) and HPLC-PAD methodology. Regarding the macrocomposition, the results revealed that most of the ground ivy dry matter was composed of insoluble dietary fibre (48.96% dmb) followed by proteins (17.92% dmb). Minerals also markedly contributed to the dry matter (12.74% dmb) with potassium as the main macroelement (48.49 mg/g dmb). Dominant phenolic compounds in ground ivy extract were: rosmarinic (6.64 mg/g dmb) and chlorogenic acid (1.11 mg/g dmb), and flavonol rutin (1.87 mg/g dmb). Fractionation of phenolic compounds from ground ivy confirmed that dominant esters were indeed those of caffeic acid, while glycosides those of quercetin, which corresponded to the majority of identified compounds in the initial extract. Insoluble-bound phenolics were not represented in notable content. This study provided additional reference for macro- and microcomponent and phenolic composition of rather underutilized but valuable medicinal plant – ground ivy, to be used in further research of its health properties.